Retaining the Readability of Cultural Words Translation: The Case of Indonesian Subtitles in Breadwinner Film - Suriadi, M. Agus; Anwar, Alma Nadia (Muslim English Literature, 2023)
This study is a translation quality assessment of cultural words translation in the Breadwinner film. It is done firstly by categorizing the cultural words and translation procedures based on Peter Newmark’s theory. Then, to find out the readability level of cultural word translation, the study uses Nababan’s theory. The data is collected by watching the film, underlining the cultural words, and classifying and tabulating the selected data in the source and target text. The film has 12 data of cultural words, which are classified into ecology, material, social, and social-political organization cultural categories. It is also found that transference, naturalization, couplet, and synonymy are categorized based on the theory. In addition, it is found that 6 data are readable, 4 are less readable, and 2 are not readable. Therefore, retaining the readability and meaning of the original text is still needed to be increased to bridge to overcome the lack of meaning in the target language as great different cultures are found, and the readability of cultural words’ translation shows that the original word plays a crucial role.